16 Rapid ambulatory physiologist-led discharge facilitating (RAPID) monitoring is a safe and efficient alternative to inpatient telemetry. (16th October 2019) - Nolan, P; Nash, P
Abstract : Background: Cardiac telemetry plays an important role during acute hospitalisation for rhythm monitoring and the diagnosis of arrhythmias. However it requires infrastructure, telemetry units, monitoring staff and bed days with their associated costs. There can be significant delays in awaiting telemetry for low to moderate risk patients and due to demand telemetry periods may be sub-optimal. Alarm fatigue amongst monitoring nurses is also recognised. To address telemetry waits, our institution commenced a Rapid Ambulatory Physiologist-led Discharge facilitating or RAPID Monitoring service, using R-test4 monitors (Novacor UK) in Jan 2019. Patients can wear these for 72hrs and can be discharged with them on. They are analysed immediately on return with teams being informed of results. Aim: This study reports on the usefulness of this alternative to inpatient telemetry. Methods: Data was collected, and continues to be collected, prospectively including -indication -number and type of significant findings-number and type of contributing findings (potential cause of initial presentation) -representation/admission rate at 30 days -length of stay -time from referral to monitor being fitted. The following clinical presentations were indicated for the RAPID Monitoring service -syncope/presyncope-TIA-Stroke Work-up-Palpitations and indications below were excluded and referred for inpatient telemetry in line with AHA Guidelines -Chest pain and ACS -known acute ventricular arrhythmias-electrolyte imbalances-atrial fibrillation with rapid ventricular response. Results: A total of 117 patients underwent RAPID monitoring between Jan and Mar 2019, representing 351 days of monitoring. The median time to fitting of the monitor from referral was 2.8 hours. Syncope/presyncope was the indication in 54% of cases, stroke and TIA accounting for 20% for referrals and palpitations being the reason in 16% of cases (figure 1 ) Significant findings on RAPID monitoring were seen in 26% of cases. These findings included atrial tachycardia (47%), atrial fibrillation or flutter (23%) and pauses >2.0s (23%). Contributing findings, a potential cause for the presentation, were found in 8% of cases. Of those patients, pauses were the most common finding (44%) followed by atrial tachycardia and atrial fibrillation, both 22% of findings (figure 2 ) Median and average length of stay were 2.0 and 5.3 days, respectively. Six patients represented acutely within 30 days (5.1%), 4 to ED, 2 to AMU with 2 requiring admission. (Note seven months of data will be available by October). Conclusion: The diagnostic yield was acceptable with significant findings being seen in 26% of patients and potential diagnostic findings in 8%. This compares well with a 5% yield in unselected syncope patients (AHA Update to Practice Standards for Electrocardiographic Monitoring in Hospital Settings 2017). Monitors were fitted quickly (median wait of 2.8 hours) and provided 72hrs of monitoring. Patients who were seen in the RAPID service had a median and average LOS (2.0 and 5.3 days) which was less than nationally reported (3.0 and 7.1 days) in 2018. The 30 day acute readmission rate of 5.1% is 54.8% lower than the national average of 11.3% (HSE 2018 Performance Reports) A RAPID monitoring service is a viable and safe alternative to inpatient telemetry, reducing waits for and demands on this service and facilitating earlier discharge.